A chewable pediatric fixed-dose combination tablet of stavudine, lamivudine, and nevirapine: Pharmacokinetics and safety compared with the individual liquid formulations in human immunodeficiency virus-infected children in Thailand - Nirun Vanprapar (2018)
Background: Pediatric fixed-dose combinations (FDCs) are needed to facilitate antiretroviral therapy in children. We evaluated the relative bioavailability, safety, and therapeutic adequacy of a novel chewable pediatric FDC tablet of stavudine (7 mg), lamivudine (30 mg), and nevirapine (50 mg), referred to as GPO-VIR S7, and compared it with the individual original brand-name liquid formulations in human immunodeficiency virus-infected Thai children. Methods: The International Maternal Pediatric Adolescent AIDS Clinical Trials group (IMPAACT) P1056 study was a phase I/II, 2-arm, randomized, open-label, multidose pharmacokinetic cross-over study. Children ≥6 to ≤30 kg receiving nevirapine-based HAART for at least 4 weeks were randomized to receive GPO-VIR S7 chewable tablets or the equivalent liquid formulations. Children were stratified by weight and dosing was weight-based. Intensive 12-hour blood sampling was performed on day 28, and subjects then crossed-over to the alternate formulation at equal doses with identical 12-hour sampling on day 56. Pharmacokinetic indices were determined by noncompartmental analysis. Results: Thirty-four children completed the study. While taking Government Pharmaceutical Organization (GPO)-VIR S7 the geometric mean (90% CI) area under the curve was 1.54 μg•hr/mL (1.42-1.67) for stavudine, 6.39 (5.82-7.00) for lamivudine, and 74.06 (65.62-83.60) for nevirapine. Nevirapine drug exposure for GPO-VIR S7 was therapeutically adequate. Geometric mean area under the curve ratios (90% CI) of GPO-VIR S7/liquid formulation for stavudine, lamivudine, and nevirapine were 0.97 (0.92-1.02), 1.41 (1.30-1.53), and 1.08 (1.04-1.13), respectively. No serious drug-related toxicity was reported. Conclusions: The chewable FDC was safe and provided therapeutically adequate plasma drug exposures in human immunodeficiency virus-infected children. Substituting the FDC for liquid formulations can simplify antiretroviral therapy. © 2010 by Lippincott Williams & Wilkins.